Particulate manganese shuttling shapes molybdenum and thallium isotope compositions in surface sediments of the Arabian Sea oxygen minimum zone - Xinming Chen; Niels A.G. M. van Helmond; Bing Xia; Hainan Lu; Zili Zhao; Yu Zhang; Lulu Wang; Yi-Bo Lin; Feifei Zhang; Gert-Jan Reichart; Caroline P. Slomp (Geochimica et Cosmochimica Acta, 2026)

Potential for Manganese Oxide Driven Anaerobic Methane Oxidation in Sediments of a Seasonally Euxinic Coastal Basin - Robin Klomp; Anna J. Wallenius; Niels A. G. M. van Helmond; Wytze K. Lenstra; Olga M. Żygadłowska; Mike S. M. Jetten; Caroline P. Slomp (Estuaries and Coasts, 2026)
Methane (CH 4 ) is a strong greenhouse gas that, in marine sediments, is produced via methanogenesis and removed via oxidation with electron acceptors such as oxygen, sulfate and metal oxides . This study assesses the potential for manganese driven anaerobic oxidation of methane (Mn-AOM) in rapidly accumulating sediments in a seasonally euxinic coastal marine basin (Scharendijke basin, Lake Grevelingen, the Netherlands). Geochemical sediment and porewater profiles demonstrate that, at the study site, Mn oxides are buried in the methanic zone. Sediment incubations amended with 13 C-CH 4 and various Mn forms indicate that the Mn oxide minerals birnessite, pyrolusite and manganite can enhance CH 4 oxidation, whereas ligand bound dissolved Mn(III) does not. This is attributed to either direct Mn-AOM, where Mn oxides act as the electron acceptor, and/or indirect Mn-driven AOM via cryptic sulfur cycling. Results of 16S rRNA gene amplicon sequencing of the incubated sediment point towards a likely role for anaerobic methanotrophic archaea of the clades ANME-2ab and ANME-3 in direct and indirect Mn-driven AOM, respectively. An increase in relative abundance of the methanogen Methanosarcina in several of the incubations suggests that these versatile methanogens benefit from Mn oxide reduction. This study demonstrates potential for Mn-driven AOM in sediments from a eutrophic, seasonally euxinic coastal basin, and expands the range of electron acceptors involved in CH 4 removal in such systems.

Biogeochemical processes in Baltic Sea sediments as a recorder of environmental change over the Holocene - Lina Piso; Ian P.G. Marshall; Caroline P. Slomp; Niels A.G.M. van Helmond (Marine Geology, 2026)

Geochemical records of Holocene environmental change in a high latitude coastal basin - Evalien Baas; Niels A.G.M. van Helmond; Marit R. van Erk; Olga M. Żygadłowska; Robin Klomp; Lina Piso; Rick Hennekam; Gert-Jan Reichart; Mike S.M. Jetten; Caroline P. Slomp (Chemical Geology, 2026)

Precession-driven variations in phosphorus cycling facilitated Earth’s oxygenation in the early Proterozoic - Wytze K. Lenstra; Margriet L. Lantink; Rick Hennekam; Paul R.D. Mason; Gert-Jan Reichart; Frederik J. Hilgen; Caroline P. Slomp (Chemical Geology, 2025)

Behaviour of cadmium isotopes in sulfidic waters and sediments of the Black Sea: Implications for global cadmium cycling and the application of cadmium isotopes as a paleo-oceanographic proxy - Alexander J. Dickson; Allison L. Bryan; Ejin George; Gideon M. Henderson; Donald Porcelli; John Rolison; Caroline P. Slomp; Rob Middag; Claudine H. Stirling (Earth and Planetary Science Letters, 2025)

Sediments From a Seasonally Euxinic Coastal Ecosystem Show High Nitrogen Cycling Potential - Isabel M. L. Rigutto; Ştefania C. Sburlan; Lars W. P. de Bont; Tom Berben; Rob M. de Graaf; Caroline P. Slomp; Mike S. M. Jetten (Environmental Microbiology, 2025)
Coastal ecosystems are susceptible to eutrophication and deoxygenation, which may alter their nitrogen cycle dynamics. Here, we investigated the microbial nitrogen cycling potential in the sediment of a seasonally euxinic coastal ecosystem (Lake Grevelingen, NL) in winter and summer. Activity tests revealed ammonium (NH 4 + ) oxidation potential with maximum potential rates up to 53 μmol g −1 day −1 , even in anoxic sediment layers. A nitrifying microbial community was present in both oxic and anoxic sediment sections (up to 1.4% relative abundance). Nitrate (NO 3 − ), nitrite (NO 2 − ), and nitrous oxide (N 2 O) reduction potential were prominent across all sediment sections, with the highest potential rates (167 μmol NO 3 −∙ g −1 day −1 ) in the surface sediment in summer. Denitrification (79.3%–98.4%) and dissimilatory nitrate reduction to ammonium (DNRA; 1.6%–20.7%) were the major NO 3 − removal pathways, as supported by the detection of the narG/napA , nirK/nirS , norB , nosZ and nrfA/otr genes in all sediment sections. The DNRA contribution increased with depth and with the addition of electron donors, such as monomethylamine. Anaerobic ammonium oxidation (anammox) was not detected in these eutrophic sediments. Combined, our results show that there is high potential for nitrogen removal in eutrophic coastal ecosystems, which may help further restoration measures.

Sedimentary vanadium depletion under sulfidic conditions: Implications for (paleo)redox proxy applications - Niels A.G.M. van Helmond; Olga M. Żygadłowska; Wytze K. Lenstra; Robin Klomp; Christoph Humborg; Daniel J. Conley; Mike S.M. Jetten; Caroline P. Slomp (Geochimica et Cosmochimica Acta, 2025)

Influence of filter backwashing on iron, manganese, and ammonium removal in dual-media rapid sand filters used for drinking water production - Alje S. Boersma; Signe Haukelidsaeter; Liam Kirwan; Alessia Corbetta; Luuk Vos; Wytze K. Lenstra; Frank Schoonenberg; Karl Borger; Paul W.J.J. van der Wielen; Maartje A.H.J. van Kessel; Caroline P. Slomp; Sebastian Lücker (Water Research, 2025)

Seasonal euxinia in a coastal basin: Impact on sedimentary molybdenum enrichments and isotope signatures - Olga M. Zygadlowska; Niels A.G.M. van Helmond; Wytze K. Lenstra; Robin Klomp; Rens Accou; Rebecca Puyk; Alexander J. Dickson; Mike S.M. Jetten; Caroline P. Slomp (Chemical Geology, 2024)

Trace metals in coastal marine sediments: Natural and anthropogenic sources, correlation matrices, and proxy potentials - K. Mareike Paul; Niels A.G.M. van Helmond; Caroline P. Slomp; Tom Jilbert (Science of The Total Environment, 2024)

Ebullition drives high methane emissions from a eutrophic coastal basin - Olga M. Żygadłowska; Jessica Venetz; Wytze K. Lenstra; Niels A.G.M. van Helmond; Robin Klomp; Thomas Röckmann; Annelies J. Veraart; Mike S.M. Jetten; Caroline P. Slomp (Geochimica et Cosmochimica Acta, 2024)

Solid phase speciation controls copper mobilisation from marine sediments by methanobactin - Danielle D. Rushworth; Walter D.C. Schenkeveld; Naresh Kumar; Vincent Noël; Jannes Dewulf; Niels A.G.M. van Helmond; Caroline P. Slomp; Moritz F. Lehmann; Stephan M. Kraemer (Science of The Total Environment, 2024)

WITHDRAWN: Seasonal euxinia in a coastal basin: Impact on sedimentary molybdenum enrichments and isotope signatures - Olga M. Zygadlowska; Niels A.G.M. van Helmond; Wytze K. Lenstra; Robin Klomp; Rens Accou; Rebecca Puyk; Alexander J. Dickson; Mike S.M. Jetten; Caroline P. Slomp (Chemical Geology, 2024)

Efficient chemical and microbial removal of iron and manganese in a rapid sand filter and impact of regular backwash - Signe Haukelidsaeter; Alje S. Boersma; Lina Piso; Wytze K. Lenstra; Niels A.G.M. van Helmond; Frank Schoonenberg; Erik van der Pol; Luis C.C. Hurtarte; Paul W.J.J. van der Wielen; Thilo Behrends; Maartje A.H.J. van Kessel; Sebastian Lücker; et al. (Applied Geochemistry, 2024)

Impact of iron addition on phosphorus dynamics in sediments of a shallow peat lake 10 years after treatment - Melanie A. Münch; Rianne van Kaam; Karel As; Stefan Peiffer; Gerard ter Heerdt; Caroline P. Slomp; Thilo Behrends (Water Research, 2024)

Anaerobic methanotrophy is stimulated by graphene oxide in a brackish urban canal sediment - Koen A. J. Pelsma; Niels A. G. M. van Helmond; Wytze K. Lenstra; Thomas Röckmann; Mike S. M. Jetten; Caroline P. Slomp; Cornelia U. Welte (Environmental Microbiology, 2023)
Anthropogenic activities are influencing aquatic environments through increased chemical pollution and thus are greatly affecting the biogeochemical cycling of elements. This has increased greenhouse gas emissions, particularly methane, from lakes, wetlands, and canals. Most of the methane produced in anoxic sediments is converted into carbon dioxide by methanotrophs before it reaches the atmosphere. Anaerobic oxidation of methane requires an electron acceptor such as sulphate, nitrate, or metal oxides. Here, we explore the anaerobic methanotrophy in sediments of three urban canals in Amsterdam, covering a gradient from freshwater to brackish conditions. Biogeochemical analysis showed the presence of a shallow sulphate–methane transition zone in sediments of the most brackish canal, suggesting that sulphate could be a relevant electron acceptor for anaerobic methanotrophy in this setting. However, sediment incubations amended with sulphate or iron oxides (ferrihydrite) did not lead to detectable rates of methanotrophy. Despite the presence of known nitrate‐dependent anaerobic methanotrophs ( Methanoperedenaceae ), no nitrate‐driven methanotrophy was observed in any of the investigated sediments either. Interestingly, graphene oxide stimulated anaerobic methanotrophy in incubations of brackish canal sediment, possibly catalysed by anaerobic methanotrophs of the ANME‐2a/b clade. We propose that natural organic matter serving as electron acceptor drives anaerobic methanotrophy in brackish sediments.

Versatile methanotrophs form an active methane biofilter in the oxycline of a seasonally stratified coastal basin - Jessica Venetz; Olga M. Żygadłowska; Wytze K. Lenstra; Niels A. G. M. van Helmond; Guylaine H. L. Nuijten; Anna J. Wallenius; Paula Dalcin Martins; Caroline P. Slomp; Mike S. M. Jetten; Annelies J. Veraart (Environmental Microbiology, 2023)
The potential and drivers of microbial methane removal in the water column of seasonally stratified coastal ecosystems and the importance of the methanotrophic community composition for ecosystem functioning are not well explored. Here, we combined depth profiles of oxygen and methane with 16S rRNA gene amplicon sequencing, metagenomics and methane oxidation rates at discrete depths in a stratified coastal marine system (Lake Grevelingen, The Netherlands). Three amplicon sequence variants (ASVs) belonging to different genera of aerobic Methylomonadaceae and the corresponding three methanotrophic metagenome‐assembled genomes (MOB‐MAGs) were retrieved by 16S rRNA sequencing and metagenomic analysis, respectively. The abundances of the different methanotrophic ASVs and MOB‐MAGs peaked at different depths along the methane oxygen counter‐gradient and the MOB‐MAGs show a quite diverse genomic potential regarding oxygen metabolism, partial denitrification and sulphur metabolism. Moreover, potential aerobic methane oxidation rates indicated high methanotrophic activity throughout the methane oxygen counter‐gradient, even at depths with low in situ methane or oxygen concentration. This suggests that niche‐partitioning with high genomic versatility of the present Methylomonadaceae might contribute to the functional resilience of the methanotrophic community and ultimately the efficiency of methane removal in the stratified water column of a marine basin.

Influence of filter age on Fe, Mn and NH4+ removal in dual media rapid sand filters used for drinking water production - Signe Haukelidsaeter; Alje S. Boersma; Liam Kirwan; Alessia Corbetta; Isaac D. Gorres; Wytze K. Lenstra; Frank K. Schoonenberg; Karl Borger; Luuk Vos; Paul W.J.J. van der Wielen; Maartje A.H.J. van Kessel; Sebastian Lücker; et al. (Water Research, 2023)

Precessional pacing of early Proterozoic redox cycles - Margriet L. Lantink; Wytze K. Lenstra; Joshua H.F.L. Davies; Rick Hennekam; David McB. Martin; Paul R.D. Mason; Gert-Jan Reichart; Caroline P. Slomp; Frederik J. Hilgen (Earth and Planetary Science Letters, 2023)

Trace metals as a redox proxy in Arabian Sea sediments in and below the oxygen minimum zone - Annika Vollebregt; Niels A.G.M. van Helmond; Susan Pit; Peter Kraal; Caroline P. Slomp (Chemical Geology, 2023)

Pathways of methane removal in the sediment and water column of a seasonally anoxic eutrophic marine basin - Olga M. Żygadłowska; Jessica Venetz; Robin Klomp; Wytze K. Lenstra; Niels A. G. M. van Helmond; Thomas Röckmann; Anna J. Wallenius; Paula Dalcin Martins; Annelies J. Veraart; Mike S. M. Jetten; Caroline P. Slomp (Frontiers in Marine Science, 2023)
Methane (CH 4 ) is a key greenhouse gas. Coastal areas account for a major proportion of marine CH 4 emissions. Eutrophication and associated bottom water hypoxia enhance CH 4 production in coastal sediments. Here, we assess the fate of CH 4 produced in sediments at a site in a seasonally anoxic eutrophic coastal marine basin (Scharendijke, Lake Grevelingen, the Netherlands) in spring (March) and late summer (September) in 2020. Removal of CH 4 in the sediment through anaerobic oxidation with sulfate ( S O 4 2 - ) is known to be incomplete in this system, as confirmed here by only slightly higher values of δ 13 C-CH 4 and δD-CH 4 in the porewater in the shallow sulfate-methane-transition zone (~5-15 cm sediment depth) when compared to deeper sediment layers. In March 2020, when the water column was fully oxygenated, CH 4 that escaped from the sediment was at least partially removed in the bottom water through aerobic oxidation. In September 2020, when the water column was anoxic below ~35 m water depth, CH 4 accumulated to high concentrations (up to 73 µmol L -1 ) in the waters below the oxycline. The sharp counter gradient in oxygen and CH 4 concentrations at ~35 m depth and increase in δ 13 C-CH 4 and δD-CH 4 above the oxycline indicate mostly aerobic water column removal of CH 4 . Water column profiles of particulate and dissolved Fe and Mn suggest redox cycling of both metals at the oxycline, pointing towards a potential role of metal oxides in CH 4 removal. Water column profiles of N H 4 + and N O 3 - indicate removal of both solutes near the oxycline. Analyses of 16S rRNA gene sequences retrieved from the water column reveal the presence of aerobic CH 4 oxidizing bacteria ( Methylomonadaceae ) and anaerobic methanotrophic archaea ( Methanoperedenaceae ), with the latter potentially capable of N O 3 - and/or metal-oxide dependent CH 4 oxidation, near the oxycline. Overall, our results indicate sediment and water column removal of CH 4 through a combination of aerobic and anaerobic pathways, which vary seasonally. Some of the CH 4 appears to escape from the surface waters to the atmosphere, however. We conclude that eutrophication may make coastal waters a more important source of CH 4 to the atmosphere than commonly assumed.

Sedimentary molybdenum and uranium: Improving proxies for deoxygenation in coastal depositional environments - K. Mareike Paul; Niels A.G.M. van Helmond; Caroline P. Slomp; Sami A. Jokinen; Joonas J. Virtasalo; Helena L. Filipsson; Tom Jilbert (Chemical Geology, 2023)

Corrigendum: Sediments as a Source of Iron, Manganese, Cobalt and Nickel to Continental Shelf Waters (Louisiana, Gulf of Mexico) - Wytze K. Lenstra; Niels A. G. M. van Helmond; Olga M. Żygadłowska; Roosmarijn van Zummeren; Rob Witbaard; Caroline P. Slomp (Frontiers in Marine Science, 2022)

Sediments as a Source of Iron, Manganese, Cobalt and Nickel to Continental Shelf Waters (Louisiana, Gulf of Mexico) - Wytze K. Lenstra; Niels A. G. M. van Helmond; Olga M. Żygadłowska; Roosmarijn van Zummeren; Rob Witbaard; Caroline P. Slomp (Frontiers in Marine Science, 2022)
Continental shelf sediments are a key source of trace metals to the ocean. In this study, we investigate the impact of sedimentary processes on water column concentrations of iron (Fe), manganese (Mn), cobalt (Co), and nickel (Ni) at five stations on the Louisiana continental shelf and slope, Gulf of Mexico. The highest trace metal concentrations were observed close to the seafloor at the most nearshore shelf station (water depth of 16 m), with most of the metals present in particulate form. This enrichment in the bottom water is likely the combined effect of input of trace metals in suspended matter from the Mississippi/Atchafalaya Rivers and, for Mn, Co, and Ni, benthic release from the shelf sediments. While particulate matter was the dominant carrier of Fe and Mn in bottom waters in the shelf and slope regions, Co and Ni were nearly exclusively present in dissolved form. Hence, lateral transport of Co and Ni in shelf waters is decoupled from that of Fe and Mn. Concentrations of particulate and dissolved trace metals in the water column generally decreased from the shelf to the slope, while those in the sediment increased. This suggests an increased retention of metals deposited on the sediment with distance from the coast, linked to the decrease in organic matter input and associated reductive sediment processes. The offshore decline in sediment trace metal mobilization is likely typical for river-dominated continental margins where most organic matter is deposited close to the coast.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Coupled dynamics of iron, manganese, and phosphorus in brackish coastal sediments populated by cable bacteria - Martijn Hermans; Marina Astudillo Pascual; Thilo Behrends; Wytze K. Lenstra; Daniel J. Conley; Caroline P. Slomp (Limnology and Oceanography, 2021)
Coastal waters worldwide suffer from increased eutrophication and seasonal bottom water hypoxia. Here, we assess the dynamics of iron (Fe), manganese (Mn), and phosphorus (P) in sediments of the eutrophic, brackish Gulf of Finland populated by cable bacteria. At sites where bottom waters are oxic in spring, surface enrichments of Fe and Mn oxides and high abundances of cable bacteria were observed in sediments upon sampling in early summer. At one site, Fe and P were enriched in a thin layer (~ 3 mm) just below the sediment–water interface. X‐ray absorption near edge structure and micro X‐ray fluorescence analyses indicate that two‐thirds of the P in this layer was associated with poorly crystalline Fe oxides, with an additional contribution of Mn(II) phosphates. The Fe enriched layer was directly overlain by a Mn oxide‐rich surface layer (~ 2 mm). The Fe oxide layer was likely of diagenetic origin, formed through dissolution of Fe monosulfides and carbonates, potentially induced by cable bacteria in the preceding months when bottom waters were oxic. Most of the Mn oxides were likely deposited from the water column as part of a cycle of repeated deposition and remobilization. Further research is required to confirm whether cable bacteria activity in spring indeed promotes the formation of distinct layers enriched in Fe, Mn, and P minerals in Gulf of Finland sediments. The temporal variations in biogeochemical cycling in this seasonally hypoxic coastal system, potentially controlled by cable bacteria activity, have little impact on permanent sedimentary Fe, Mn, and P burial.

Coastal hypoxia and eutrophication as key controls on benthic release and water column dynamics of iron and manganese - Wytze K. Lenstra; Martijn Hermans; Marie J.M. Séguret; Rob Witbaard; Silke Severmann; Thilo Behrends; Caroline P. Slomp (Limnology and Oceanography, 2021)
Continental shelves are a major source of iron (Fe) and manganese (Mn) to marine waters. Here, we investigate controls on benthic release of Fe and Mn and the impact on the water column in the Baltic Sea. We find high in situ benthic release rates of dissolved Fe and Mn at seasonally hypoxic sites (bottom water oxygen between 0–63 μ mol L −1 ) receiving high inputs of organic matter. We find that benthic Fe and Mn release is sensitive to bottom water oxygen concentrations. Benthic Fe release is likely additionally controlled by Fe–sulfur redox chemistry in the surface sediment. For Mn, benthic release correlates positively with Mn oxide availability in the surface sediment. Benthic release contributes to high dissolved Fe and Mn concentrations in the water column and is amplified by repeated cycling of Fe and Mn between the sediment and overlying water through benthic release, oxidation in the water column, deposition as metal oxides, followed by reductive dissolution. Most water column Fe (∼ 80%) is present in particulate form near the seafloor. In contrast to Fe, a large percentage of the Mn remains dissolved (∼ 50%). We show that easily reducible Fe and Mn oxides are key forms of particulate Fe and Mn in suspended matter. The Baltic Sea represents a highly eutrophic, low oxygen end‐member when compared to other modern coastal systems. Our results imply that, upon continued eutrophication and deoxygenation of the coastal ocean, benthic release of dissolved Fe and Mn from continental shelves could become greater than previously thought.

Recovery from multi‐millennial natural coastal hypoxia in the Stockholm Archipelago, Baltic Sea, terminated by modern human activity - Niels A. G. M. van Helmond; Bryan C. Lougheed; Annika Vollebregt; Francien Peterse; Guillaume Fontorbe; Daniel J. Conley; Caroline P. Slomp (Limnology and Oceanography, 2020)
Enhanced nutrient input and warming have led to the development of low oxygen (hypoxia) in coastal waters globally. For many coastal areas, insight into redox conditions prior to human impact is lacking. Here, we reconstructed bottom water redox conditions and sea surface temperatures (SSTs) for the coastal Stockholm Archipelago over the past 3000 yr. Elevated sedimentary concentrations of molybdenum indicate (seasonal) hypoxia between 1000 b.c.e. and 1500 c.e . Biomarker‐based (TEX 86 ) SST reconstructions indicate that the recovery from hypoxia after 1500 c.e. coincided with a period of significant cooling (∼ 2°C), while human activity in the study area, deduced from trends in sedimentary lead and existing paleobotanical and archeological records, had significantly increased. A strong increase in sedimentary lead and zinc, related to more intense human activity in the 18 th and 19 th century, and the onset of modern warming precede the return of hypoxia in the Stockholm Archipelago. We conclude that climatic cooling played an important role in the recovery from natural hypoxia after 1500 c.e. , but that eutrophication and warming, related to modern human activity, led to the return of hypoxia in the 20 th century. Our findings imply that ongoing global warming may exacerbate hypoxia in the coastal zone of the Baltic Sea.

Understanding Environmental Changes in Temperate Coastal Seas: Linking Models of Benthic Fauna to Carbon and Nutrient Fluxes - Eva Ehrnsten; Xiaole Sun; Christoph Humborg; Alf Norkko; Oleg P. Savchuk; Caroline P. Slomp; Karen Timmermann; Bo G. Gustafsson (Frontiers in Marine Science, 2020)

Factors regulating the coastal nutrient filter in the Baltic Sea - Jacob Carstensen; Daniel J. Conley; Elin Almroth-Rosell; Eero Asmala; Erik Bonsdorff; Vivi Fleming-Lehtinen; Bo G. Gustafsson; Camilla Gustafsson; Anna-Stiina Heiskanen; Urzsula Janas; Alf Norkko; Caroline Slomp; et al. (Ambio, 2020)
The coastal zone of the Baltic Sea is diverse with strong regional differences in the physico-chemical setting. This diversity is also reflected in the importance of different biogeochemical processes altering nutrient and organic matter fluxes on the passage from land to sea. This review investigates the most important processes for removal of nutrients and organic matter, and the factors that regulate the efficiency of the coastal filter. Nitrogen removal through denitrification is high in lagoons receiving large inputs of nitrate and organic matter. Phosphorus burial is high in archipelagos with substantial sedimentation, but the stability of different burial forms varies across the Baltic Sea. Organic matter processes are tightly linked to the nitrogen and phosphorus cycles. Moreover, these processes are strongly modulated depending on composition of vegetation and fauna. Managing coastal ecosystems to improve the effectiveness of the coastal filter can reduce eutrophication in the open Baltic Sea.

Enhanced Organic Carbon Burial in Sediments of Oxygen Minimum Zones Upon Ocean Deoxygenation - Itzel Ruvalcaba Baroni; Virginia Palastanga; Caroline P. Slomp (Frontiers in Marine Science, 2020)

Microbial community composition and functional potential in Bothnian Sea sediments is linked to Fe and S dynamics and the quality of organic matter - Olivia Rasigraf; Niels A. G. M. van Helmond; Jeroen Frank; Wytze K. Lenstra; Matthias Egger; Caroline P. Slomp; Mike S. M. Jetten (Limnology and Oceanography, 2020)
The Bothnian Sea is an oligotrophic brackish basin characterized by low salinity and high concentrations of reactive iron, methane, and ammonium in its sediments, enabling the activity and interactions of many microbial guilds. Here, we studied the microbial network in these sediments by analyzing geochemical and microbial community depth profiles at one offshore and two near coastal sites. Analysis of 16S rRNA gene amplicons revealed a distinct depth stratification of both archaeal and bacterial taxa. The microbial communities at the two near coastal sites were more similar to each other than the offshore site, which is likely due to differences in the quality and rate of organic matter degradation. The abundance of methanotrophic archaea of the ANME‐2a clade was shown to be related to the presence of methane and varied with sediment iron content. Metagenomic sequencing of sediment‐derived DNA from below the sulfate–methane transition zone revealed a broad potential for respiratory sulfur metabolism via partially reduced sulfur species. The potential for nitrogen cycling was dominated by reductive processes via a truncated denitrification pathway encoded exclusively by bacterial lineages. Gene‐centric fermentative metabolism analysis indicated a potential importance for acetate, formate, alcohol, and hydrogen metabolism. Methanogenic/‐trophic pathways were dominated by Methanosaetaceae , Methanosarcinaceae , Methanomassiliicoccaceae , Methanoregulaceae , and ANME‐2 archaea. Our results indicated flexible metabolic capabilities of core microbial community taxa, which could adapt to changing redox conditions, and with a spatial and depth distribution that is likely governed by the quality and input of available organic substrates and, for ANME‐2, of iron oxides.

A reply to the comment by Karlsson et al. - Eero Asmala; Jacob Carstensen; Daniel J. Conley; Caroline P. Slomp; Johanna Stadmark; Maren Voss (Limnology and Oceanography, 2019)

Phosphorus Cycling and Burial in Sediments of a Seasonally Hypoxic Marine Basin - Fatimah Sulu-Gambari; Mathilde Hagens; Thilo Behrends; Dorina Seitaj; Filip J. R. Meysman; Jack Middelburg; Caroline P. Slomp (Estuaries and Coasts, 2018)

Holocene Refreshening and Reoxygenation of a Bothnian Sea Estuary Led to Enhanced Phosphorus Burial - Nikki Dijkstra; Nadine B. Quintana Krupinski; Masako Yamane; Stephen P. Obrochta; Yosuke Miyairi; Yusuke Yokoyama; Caroline P. Slomp (Estuaries and Coasts, 2018)

Efficiency of the coastal filter: Nitrogen and phosphorus removal in the Baltic Sea - Eero Asmala; Jacob Carstensen; Daniel J. Conley; Caroline P. Slomp; Johanna Stadmark; Maren Voss (Limnology and Oceanography, 2017)
An important function of coastal ecosystems is the reduction of the nutrient flux from land to the open sea, the coastal filter. In this study, we focused on the two most important coastal biogeochemical processes that remove nitrogen and phosphorus permanently: denitrification and phosphorus burial. We compiled removal rates from coastal systems around the Baltic Sea and analyzed their spatial variation and regulating environmental factors. These analyses were used to scale up denitrification and phosphorus burial rates for the entire Baltic Sea coastal zone. Denitrification rates ranged from non‐detectable to 12 mmol N m −2 d −1 , and correlated positively with both bottom water nitrate concentration and sediment organic carbon content. The rates exhibited a strong decreasing gradient from land to the open coast, which was likely driven by the availability of nitrate and labile organic carbon, but a high proportion of non‐cohesive sediments in the coastal zone decreased the denitrification efficiency relative to the open sea. Phosphorus burial rates varied from 0.21 g P m −2 yr −1 in open coastal systems to 2.28 g P m −2 yr −1 in estuaries. Our analysis suggests that archipelagos are important phosphorus traps and account for 45% of the coastal P removal, while covering only 17% of the coastal areas. High burial rates could partly be sustained by phosphorus import from the open Baltic Sea. We estimate that the coastal filter in the Baltic Sea removes 16% of nitrogen and 53% of phosphorus inputs from land.

Sedimentary oxygen dynamics in a seasonally hypoxic basin - Dorina Seitaj; Fatimah Sulu‐Gambari; Laurine D. W. Burdorf; Alicia Romero‐Ramirez; Olivier Maire; Sairah Y. Malkin; Caroline P. Slomp; Filip J. R. Meysman (Limnology and Oceanography, 2017)
Seasonal hypoxia refers to the oxygen depletion that occurs in summer in the bottom water of stratified systems, and is increasingly observed in coastal areas worldwide. The process induces a seasonal cycle on the biogeochemistry of the underlying sediments, which remains poorly quantified. Here, we investigated the sedimentary oxygen consumption within Lake Grevelingen (The Netherlands), a saline coastal reservoir that is impacted by yearly recurrent bottom water hypoxia. Monthly sampling campaigns were conducted throughout 2012 at three sites along a depth gradient. Macrofauna sampling and sediment profile imaging demonstrated how summer hypoxia strongly impacts the benthic communities below 15 m of water depth. Benthic fluxes of oxygen, dissolved inorganic carbon, total alkalinity, and ammonium were determined by closed core incubations, while oxygen depth profiles were recorded by microsensor profiling of sediment cores. Our results reveal a pronounced seasonality in the sedimentary oxygen consumption. Low uptake rates in summer were caused by oxygen limitation, and resulted in the build‐up of an “oxygen debt” through the accumulation of reduced iron sulfides. Highest oxygen uptake rates were recorded in fall, linked to the reoxidation of the pool of iron sulfides in the top layer. However, uptake rates remained unexpectedly high during winter and early spring, likely associated with the oxidation of iron sulfides down to centimeters depth due to the electrogenic sulfur oxidation by cable bacteria. Overall, our results suggest that the sedimentary oxygen dynamic in seasonally hypoxic coastal systems is characterized by a strongly amplified “oxygen debt” dynamics induced by cable bacteria.

Iron‐dependent anaerobic oxidation of methane in coastal surface sediments: Potential controls and impact - Jurjen Rooze; Matthias Egger; Iana Tsandev; Caroline P. Slomp (Limnology and Oceanography, 2016)
Anaerobic oxidation of methane (AOM) is an important process of methane (CH 4 ) removal in sediments. Various studies suggest that AOM coupled to iron oxide (Fe(OH) 3 ) reduction (Fe‐AOM) may complement sulfate‐driven AOM in CH 4 ‐rich sediments. Here, we apply a transient reaction‐transport model to depth profiles of key porewater and sediment constituents for a site in the Bothnian Sea where Fe‐AOM has been suggested to occur. At the site, increased eutrophication has led to an upward shift of the sulfate‐methane transition zone, submerging Fe(OH) 3 in a zone with high CH 4 concentrations. Fe‐AOM is thought to lead to a strong accumulation of dissolved iron (Fe 2+ ) in the porewater. Results of a sensitivity analysis identify three potential controls on the occurrence of Fe‐AOM in coastal surface sediments: (1) bottom‐water sulfate ( ) concentrations, (2) Fe(OH) 3 availability, and (3) organic matter (OM) loading. In‐situ CH 4 production is particularly sensitive to the OM loading and bottom‐water concentration, with higher concentrations significantly inhibiting methanogenesis and decreasing the potential rates of Fe‐AOM. We find that only environments with a low salinity and a relatively high Fe(OH) 3 loading allow for Fe‐AOM to occur in surface sediments. This suggests that Fe‐AOM in surface sediments is restricted to areas with relatively high rates of sediment deposition such as estuaries and other nearshore systems. By enhancing porewater Fe 2+ concentrations in surface sediments and the flux of Fe 2+ from sediments to the overlying water, Fe‐AOM may contribute to the lateral transfer of iron (“iron shuttling”) from the coastal zone to deep basins.

Evolving coastal character of a Baltic Sea inlet during the Holocene shoreline regression: impact on coastal zone hypoxia - Wenxin Ning; Anupam Ghosh; Tom Jilbert; Caroline P. Slomp; Mansoor Khan; Johan Nyberg; Daniel J. Conley; Helena L. Filipsson (Journal of Paleolimnology, 2016)

Eutrophication-Driven Deoxygenation in the Coastal Ocean - Nancy Rabalais; Wei-Jun Cai; Jacob Carstensen; Daniel Conley; Brian Fry; Xinping Hu; Zoraida Quiñones-Rivera; Rutger Rosenberg; Caroline Slomp; Eugene Turner; Maren Voss; Björn Wissel; et al. (Oceanography, 2014)

Hypoxia in the Baltic Sea: Biogeochemical Cycles, Benthic Fauna, and Management - Jacob Carstensen; Daniel J. Conley; Erik Bonsdorff; Bo G. Gustafsson; Susanna Hietanen; Urzsula Janas; Tom Jilbert; Alexey Maximov; Alf Norkko; Joanna Norkko; Daniel C. Reed; Caroline P. Slomp; et al. (Ambio, 2014)

A welcome can of worms? Hypoxia mitigation by an invasive species - Joanna Norkko; Daniel C. Reed; Karen Timmermann; Alf Norkko; Bo G. Gustafsson; Erik Bonsdorff; Caroline P. Slomp; Jacob Carstensen; Daniel J. Conley (Global Change Biology, 2012)
Invasive species and bottom‐water hypoxia both constitute major global threats to the diversity and integrity of marine ecosystems. These stressors may interact with unexpected consequences, as invasive species that require an initial environmental disturbance to become established can subsequently become important drivers of ecological change. There is recent evidence that improved bottom‐water oxygen conditions in coastal areas of the northern Baltic Sea coincide with increased abundances of the invasive polychaetes M arenzelleria spp. Using a reactive‐transport model, we demonstrate that the long‐term bioirrigation activities of dense M arenzelleria populations have a major impact on sedimentary phosphorus dynamics. This may facilitate the switch from a seasonally hypoxic system back to a normoxic system by reducing the potential for sediment‐induced eutrophication in the upper water column. In contrast to short‐term laboratory experiments, our simulations, which cover a 10‐year period, show that M arenzelleria has the potential to enhance long‐term phosphorus retention in muddy sediments. Over time bioirrigation leads to a substantial increase in the iron‐bound phosphorus content of sediments while reducing the concentration of labile organic carbon. As surface sediments are maintained oxic, iron oxyhydroxides are able to persist and age into more refractory forms. The model illustrates mechanisms through which M arenzelleria can act as a driver of ecological change, although hypoxic disturbance or natural population declines in native species may be needed for them to initially become established. Invasive species are generally considered to have a negative impact; however, we show here that one of the main recent invaders in the Baltic Sea may provide important ecosystem services. This may be of particular importance in low‐diversity systems, where disturbances may dramatically alter ecosystem services due to low functional redundancy. Thus, an environmental problem in one region may be either exacerbated or alleviated by a single species from another region, with potentially ecosystem‐wide consequences.

Phosphatases relieve carbon limitation of microbial activity in Baltic Sea sediments along a redox‐gradient - Anne K. Steenbergh; Paul L. E. Bodelier; Hans L. Hoogveld; Caroline P. Slomp; Hendrikus J. Laanbroek (Limnology and Oceanography, 2011)
The relationship between phosphatase activity and the element limiting microbial activity (carbon [C], nitrogen [N], or phosphorus [P]) was studied experimentally in sediment from four stations in the Baltic Sea located along a depth transect from oxic to anoxic bottom waters. The role of extracellular phosphatases was assessed by determining the percentages of intact cells that could be labeled with an artificial substrate for phosphatases (i.e., enzyme‐labeled fluorescence 97 phosphatase substrate [ELF]) using a flow cytometer. Phosphatase activity was detected in sediment slurries from all sites either with or without prior incubation under oxic or anoxic conditions. In addition, ELF‐labeled cells were detected in all incubated sediments, indicating that intact cells bearing phosphatases contribute to the phosphatase activity. Phosphatase activities and percentages of ELF‐labeled cells were lower for the anoxic than for the oxic slurry incubations. Phosphatases are likely used to relieve the limitation of microbial activity by utilizable C in these recently deposited, organic C‐rich sediments in the Baltic Sea. In marine sediments overlain by anoxic bottom waters, the biological and chemical mechanisms of P retention are often less efficient than in oxic settings and the P released to relieve C limitation escapes to the overlying water. This explains the ongoing higher P fluxes from sediments overlain by anoxic bottom waters.

Worldwide Typology of Nearshore Coastal Systems: Defining the Estuarine Filter of River Inputs to the Oceans - Hans H. Dürr; Goulven G. Laruelle; Cheryl M. van Kempen; Caroline P. Slomp; Michel Meybeck; Hans Middelkoop (Estuaries and Coasts, 2011)

Sedimentary phosphorus dynamics and the evolution of bottom‐water hypoxia: A coupled benthic–pelagic model of a coastal system - Daniel C. Reed; Caroline P. Slomp; Bo G. Gustafsson (Limnology and Oceanography, 2011)
The present study examines oxygen and phosphorus dynamics at a seasonally hypoxic site in the Arkona basin of the Baltic Sea. A coupled benthic–pelagic reactive‐transport model is used to describe the evolution of bottom‐water solute concentrations, as well as pore‐water and sediment profiles. Aerobic respiration dominates remineralization, with iron reduction, denitrification, and sulphate reduction playing secondary roles, while other pathways are negligible. Sediments represent a significant oxygen sink chiefly due to the aerobic degradation of organic matter, as well as nitrification and iron oxyhydroxide precipitation. Most phosphorus deposited in sediments is in organic matter, yet cycling is dominated by iron‐bound phosphorus due to rapid dissimilatory iron reduction coupled with aerobic iron oxyhydroxide formation. Sustained hypoxia results in an initial decrease in sediment phosphorus content due to dissolution of phosphorus‐bearing iron oxyhydroxides, resulting in a pulse of phosphate to overlying waters. Although an organic‐rich layer is formed under low‐oxygen conditions, enhanced remineralization of organic phosphorus relative to organic carbon tempers sedimentary phosphorus accumulation. Upon reoxygenation of bottom waters after a decade of sustained hypoxia, oxygen concentrations do not immediately achieve values observed prior to hypoxia because the organic‐rich layer creates a higher benthic oxygen demand. Artificial reoxygenation of bottom waters leads to a substantial increase in the iron‐bound phosphorus pool; the total phosphorus content of the sediment, however, is unaffected. A relapse into hypoxia would consequently produce a large pulse of phosphate to the overlying waters potentially exacerbating the situation.

Modeling nitrogen cycling in a coastal fresh water sediment - Richard W. Canavan; Anniet M. Laverman; Caroline P. Slomp (Hydrobiologia, 2007)